2013
DOI: 10.1590/s0006-87052013005000007
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de cultivares de café resistentes à ferrugem no estado de Minas Gerais, Brasil

Abstract: ResumoObjetivou-se no trabalho avaliar o comportamento de 24 cultivares de cafeeiro, sendo 22 resistentes à ferrugem e duas testemunhas suscetíveis, em diferentes ambientes de Minas Gerais, a fim de contribuir para a recomendação técnica. Os experimentos foram instalados em quatro municípios (Lavras, Campos Altos, Patrocínio e Turmalina). O delineamento experimental utilizado foi o de blocos casualizados com três repetições, no espaçamento de 3,5x0,7 m e parcelas de dez plantas. As avaliações de produtividade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 13 publications
6
37
0
6
Order By: Relevance
“…'IPR 102' mostly stood out in Mandaguari, since at the spacing 2.5 x 0.5 m, IPR 103 did not differ from IAPAR 59 and Catuaí, while IPR 102 differed from these two cultivars. Moreover, in Mandaguari, at the spacing of 3 x 0.5 m, IPR 102 had higher yield than 'IPR 103', which is a cultivar with high yield in different cultivation environments of Brazil, in the states of Paraná (Sera et al 2013), Minas Gerais (Carvalho et al 2012), and Rio de Janeiro (Rodrigues et al 2014). In Londrina, IPR 102 did not differ from IPR 103, and in Itaguajé, IPR 103 had higher yield than IPR 102.…”
Section: Pedigree and Improvement Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…'IPR 102' mostly stood out in Mandaguari, since at the spacing 2.5 x 0.5 m, IPR 103 did not differ from IAPAR 59 and Catuaí, while IPR 102 differed from these two cultivars. Moreover, in Mandaguari, at the spacing of 3 x 0.5 m, IPR 102 had higher yield than 'IPR 103', which is a cultivar with high yield in different cultivation environments of Brazil, in the states of Paraná (Sera et al 2013), Minas Gerais (Carvalho et al 2012), and Rio de Janeiro (Rodrigues et al 2014). In Londrina, IPR 102 did not differ from IPR 103, and in Itaguajé, IPR 103 had higher yield than IPR 102.…”
Section: Pedigree and Improvement Methodsmentioning
confidence: 87%
“…Sabiá 398 had higher yield than Catuaí Amarelo IAC 74 in the municipality of Varginha, Minas Gerais, Brazil (Paiva et al 2010). In a study carried out in four environments in the state of Minas Gerais, it was observed that Sabiá Tardio, Pau Brasil MG1, Obatã IAC 1669-20, Catucaí Amarelo 24/137 and IPR 103 stood out for having the greatest yield, with stability and adaptability, regardless of the environment (Carvalho et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…For the species, C. arabica, the expression of several agronomic traits have been reported to be highly related to the expression of genetic diversity among cultivars (Carvalho et al, 2012;DaMatta, 2004;Del Grossi et al, 2013;Martinez et al, 2011;Martins et al, 2015;Rodrigues et al, 2014Rodrigues et al, , 2015Shigueoka et al, 2014). Additionally, the estimative of coefficient of genotypic determinations were higher than 90% for MRR, LFG and BER ( Table 1), showing that these traits are especially valuable in the genetic study of the recovery, since genetic factors seems to have major contribution in the determination of the phenotypic values of these traits.…”
Section: Resultsmentioning
confidence: 99%
“…plantations in Brazil . Possessing high potential, vegetative vigor, and beverage quality, these cultivars have shown wide adaptability and phenotypic stability in different coffee regions of the country (ANDRADE et al., 2013;BOTELHO et al, 2010a). Nevertheless, they are also susceptible to coffee leaf rust caused by the fungus Hemileia vastatrix Berk.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic resistance is considered to be one of the most efficient, environmentally safe, and economically viable measures in the management of those pathogens (ALPIZAR et al, 2007;BOISSEAU et al, 2009;CARVALHO et al, 2012). The Timor Hybrid (TH), most likely a natural cross between Coffea Arabica and C. canephora Pierre ex A. Froehner, is a source of genetic material for the development of new cultivars (RODRIGUES JÚNIOR et al, 2004).…”
Section: Introductionmentioning
confidence: 99%